Synthesis of Phosphatidylcholines Possessing Functionalized Acids at sn-2, and 13C–14N and 13C–31P Couplings in Their 13C NMR Spectra - Morita, Masao; Saito, Shun; Shinohara, Riku; Aoyagi, Ryohei; Arita, Makoto; Kobayashi, Yuichi (Synlett, 2020)
Although 4-Me2NC5H4N (DMAP) is a standard base for esterification of (2-Me-6-NO2-C6H3CO)2O (MNBA), N-methylimidazole (NMI) was examined for the condensation of acids with 1-stearoyl-lysophosphatidylcholine because of the non-tailing nature of NMI on silica gel. Acids tested were EPA, α-linolenic acid, TBS ethers of 18-HEPE and ricinoleic acid, acid-labile epoxy acids, and a phenyldiynyl acid. The condensation proceeded well with these acids, and chromatographic separation of resulting phosphatidylcholines and remaining NMI was easily performed. During the characterization of the products by 13C NMR spectroscopy, 13C–14N and 13C–31P couplings were observed.
Keywords: synthesis; lyso-phosphatidylcholine; functionalized acid; Shiina reagent; N-methylimidazole; 13C–14N coupling